Drug utilization in emergency medicine department at a tertiary care teaching hospital: A prospective study - Barot, Preksha A. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND AND OBJECTIVES: The practice of emergency medicine has the primary mission of evaluating, managing and providing treatment to those patients with unexpected injury or illness. Instituting appropriate therapy is necessary for safety of the patients and to decrease mortality and morbidity. The objectives were to study the drug utilization pattern and direct cost of therapy in emergency medicine department of a tertiary care teaching hospital. MATERIALS AND METHODS: Data of the patients admitted to emergency medicine department was collected prospectively for 48 h from the time of admission over 2 months. The prescriptions were analyzed for drug use pattern and direct cost of therapy was calculated. RESULTS: A total of 156 patients received 1635 drugs with the mean of 9.99 ± 2.55 drugs/patient. Most common diagnosis was acute coronary syndrome 35 (21.79%). Ondansetron 135 (86.53%) was most frequently prescribed drug followed by pantoprazole 133 (85.25%) and furosemide 68 (43.58%). Amongst antimicrobials ceftriaxone 51 (32.69%) was the most commonly prescribed drug. Direct cost of treatment per patient for the first 48 h was र 4051 ± 1641. CONCLUSION: Ondansetron and pantoprazole were the most commonly prescribed drugs in the emergency department. However, their use in all patients was not justified. Polypharmacy was prevalent. A closer look at the rationality of therapy would help in highlighting issues involved and would be helpful to authorities in deciding prescribing policies.